THE INFLUENCE OF THE PHYSICAL AND VIRTUAL ENVIRONMENT IN THE DEVELOPMENT OF STUDENTS ACCORDING TO ISLAMIC EDUCATION PERSPECTIVES - Sugiarto, Wahyu; Ru'iya, Sutipyo; Herbanu, Rashid; Mahmuda, Ibn (Universitas Islam Negeri Alauddin Makassar, 2022)
The influence of the physical environment (family, school, community) in the development of students is very large, especially in the modern era like now with the virtual world environment. Where is this virtual environment a person can find out something outside of their existence. This paper is designed to find out how much influence the above environment has on the development of students in the perspective of Islamic education. In writing this paper using the library method by taking a variety of existing literature on google schooler. The results of the research from the preparation of this paper as a reference in educating students by following its development while maintaining Islamic values in its development in the world of education.